ANTIHYPERTENSIVE EFFICACY AND SAFETY OF OLMESARTAN MEDOXOMIL AND RAMIPRIL IN ELDERLY PATIENTS WITH MILD TO MODERATE ESSENTIAL HYPERTENSION: THE ESPORT STUDY - E. Malacco; S. Omboni; M. Volpe; A. Auteri; A. Zanchetti (Российский кардиологический журнал, 2012)
Objective. To compare the efficacy and safety of the angiotensin II antagonist olmesartan medoxomil (O) and the ACE inhibitor ramipril (R) in elderly patients with essential arterial hypertension. Methods. After a 2-week placebo wash-out 1102 treated or untreated elderly hypertensive patients aged 65–89 years (office sitting diastolic blood pressure, DBP, 90–109mmHg and/or office sitting systolic blood pressure, SBP, 140–179mmHg) were randomized double-blind to 12-week treatment with O 10mg or R 2.5mg oncedaily. After the first 2 and 6 weeks doses could be doubled in non-normalized [blood pressure (BP) <140/90mmHg for nondiabetic and<130/80mmHg for diabetic) individuals, up to 40mg for O and 10mg for R. Office BPs were assessed at randomization, after 2, 6 and 12 weeks of treatment, whereas 24-h ambulatory BP was recorded at randomization and after 12 weeks. Results. In the intention-to-treat population (542 patients O and 539 R) after 12 weeks of treatment baseline-adjusted office SBP and DBP reductions were greater (P<0.01) with O [17.8 (95% confidence interval: 16.8/18.9) and 9.2 (8.6/9.8) mmHg] than with R [15.7 (14.7/16.8) and 7.7 (7.1/8.3) mmHg]. BP normalization rate was also greater under O (52.6 vs. 46.0% R, P<0.05). In the subgroup of patients with valid ambulatory BP recording (318 O and 312 R) the reduction in 24-h average BP was larger (P<0.05) with O [SBP: 11.0 (12.2/9.9) and DBP: 6.5 (7.2/5.8) mmHg] than with R [9.0 (10.2/7.9) and 5.4 (6.1/4.7) mmHg]. The larger blood pressure reduction obtained with O was particularly evident in the last 6 h from the dosing interval; a better homogeneity of the 24-h BP control with O was confirmed by higher smoothness indices. The proportion of patients with drug-related adverse events was comparable in the two groups (3.6 O vs. 3.6% R), as well as the number of patients discontinuing study drug because of a side effect (14 O vs. 19 R). Conclusion. In elderly patients with essential arterial hypertension O provides an effective, prolonged and well tolerated BP control, representing a useful option among first-line drug treatments of hypertension in this age group.